Pastagem de Brachiaria Brizantha fertirrigada com dejetos líquidos de suínos - Medeiros, Lucilene Tavares (2004)
This research took place in a private rural property located in the municipal district of Alfenas-MG in the experimental period from August 2003 to June 2004 The aim was to evaluate the use of liquid swine dejections in the lining matter productivity (MS) and the following bromatological characteristics dry matter percentage (BAD) rude protein content (PB) fiber in neutral detergent (FDN) fiber in acid detergent (FDA) and in vitro digestibility of the dry matter (DIVMS) of the forage Brachiaria brizantha cv Marandu The experimental delineation was in casualized blocks with portions subdivided in time with nine treatments and four repetitions The portions comprised the treatments (frequency of dejections application) and the sub portions and the times of forage cut The treatments were T1 (I use of limestone)T2 (chemical manuring - 100-40e 6kg/ha of NPK) T3 (180 m³/ha/1x/year - fermented for 45 days) T4 (180 m³/ha/2x/ year T5 (180 m³/ha/3x/ year T6 (180 m³/ha/4x/ year T7 (180 m³/ha/5x/ year T8 (180 m³/ha/1x/ year - in natura T9 (witness) For average comparisons the computational program "SISVAR" was used (FERREIRA 2000) and the used test was Scott-Knott The soil correction was accomplished in each portion where three tons/ha of dolomitic limestone has been used by hectare A maximum dosage of 180 m³/ha/year of liquid swine dejections was used at once and also parceled out in five times a year In the chemical manuring 100 40 and 60 kg/ha of NPK were used in the forms of sulfate of ammonium super simple and potassium chloride respectively at once Every 45 days after first manuring the forage cuts were performed for productivity determination and samples for laboratorial analyses were retreated The number of perfilhos/m² was superior in the treatments where the dejections were used in one-dosage and the productivity of dry matter was also superior in the treatments that the one-dosage was used as in the first and as in the second cutting times The witness treatment and the one where only limestone was used presented the largest percentage of MS in the first and third cutting times in the second and fourth times the witness treatment showed larger percentage of MS and the smallest percentage of MS were observed in the treatments that used larger dosages of liquid swine dejections in the beginning of the experimental period The treatments 3 8 and 4 180 m³/ha/year fermented for 45 days 180 m³/ha/year "in natura" and 180 m³/ha / 2x/year respectively showed superiority in the content of rude protein (PB) in the first and second cutting times The largest fiber values in neutral detergent (FDN) were observed in the second cutting time with tendency of decreasing throughout the cutting times Overall the smallest fiber values in acid detergent (FDA) were observed in the treatments that used dejections 2x/year (T4) and 5x/year (T5) in the first cutting time The largest coefficients of "in vitro" digestibility of the dry matter e (DIVMS) were observed in the treatments 3 4 and 8 in the first cutting time, and a tendency of decreasing throughout the cutting times being observed Concerning the agronomic and bromatological characteristics the best results were observed in the treatments that 180 m³/ha of liquid swine dejections were used at once fermented for 45 days and in natura in the beginning of the rainy period